2011
DOI: 10.1523/jneurosci.6577-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Erythroid 2-Related Factor 2 Facilitates Neuronal Glutathione Synthesis by Upregulating Neuronal Excitatory Amino Acid Transporter 3 Expression

Abstract: Astrocytes support neuronal antioxidant capacity by releasing glutathione, which is cleaved to cysteine in brain extracellular space. Free cysteine is then taken up by neurons through excitatory amino acid transporter 3 [EAAT3; also termed Slc1a1 (solute carrier family 1 member 1)] to support de novo glutathione synthesis. Activation of the nuclear factor erythroid 2-related factor 2 (Nrf2)-antioxidant responsive element (ARE) pathway by oxidative stress promotes astrocyte release of glutathione, but it remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 53 publications
5
67
0
Order By: Relevance
“…Recent in vivo evidence also supports a role for activation of the Nrf2 pathway in increasing CNS GSH levels. These data suggested that enhanced astrocyte GSH biosynthesis and secretion led to increased extracellular cysteine as a product of GSH metabolism, which was then transported into neurons via up-regulation of the excitatory amino acid transporter 3, and ultimately drove increased neuronal GSH due to increased levels of biosynthetic substrate (Escartin et al, 2011). Elucidation of this pathway suggests a potential role for cell type-specific neuroprotective responses and is consistent with the astrocyte data presented here.…”
Section: Discussionsupporting
confidence: 85%
“…Recent in vivo evidence also supports a role for activation of the Nrf2 pathway in increasing CNS GSH levels. These data suggested that enhanced astrocyte GSH biosynthesis and secretion led to increased extracellular cysteine as a product of GSH metabolism, which was then transported into neurons via up-regulation of the excitatory amino acid transporter 3, and ultimately drove increased neuronal GSH due to increased levels of biosynthetic substrate (Escartin et al, 2011). Elucidation of this pathway suggests a potential role for cell type-specific neuroprotective responses and is consistent with the astrocyte data presented here.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, under the deprivation of extracellular glucose, guanosine modulated the EAAC1 (EAAT3) levels. Although this transporter is responsible for the support of de novo GSH synthesis, it is also sensitive to oxidative stress [105]. Typically, the activation of PKC and PI3K pathways regulates the expression of EAAC1 [13,66].…”
Section: Discussionmentioning
confidence: 99%
“…Striata were rapidly dissected out on ice and homogenized in 50 mM Tris-HCl, pH 7.4, 100 mM NaCl, and 1% SDS, with protease inhibitor cocktail (Roche). Western blots were performed using ECL detection as described previously (Escartin et al, 2011) using antibodies against actin (1:5000) and TSPO (1:500).…”
Section: Methodsmentioning
confidence: 99%